الإعلام بين فلسفة القانون وقواعد الأخلاق - عزوق, الخير (revue mofakir; No 07 (2011): مجلة المفكر, 2018)
الملخص : تعالج هذه المقالة المخصصة للإعلام بين فلسفة القانون ومدونات الأخلاقيات المهنية، الارتباطات العضوية والوظيفية التي تصل الإعلام بالقانون رغم الأسبقية التاريخية لعلم القانون على الإعلام، ورغم التفاعلات الموجودة بين هذين الفرعين من فروع العلوم الإنسانية، كما هو الشأن بينها وبين مدونات الأخلاقيات.   Abstract : - This article on “The Information between the Law philosophy and the Codes of Ethics” deals, as it does, with the organic and functional links connecting it to the law even though the science of law had ، historically preceded the Information and despite the interactions between the two branches of the human sciences; as well as the codes of professional ethics.